The power of Psalms in post-biblical Judaism: liturgy, ritual and community - Bergmann, Claudia D.; Rajak, Tessa; Kranemann, Benedikt; Ullrich, Rebecca (Ancient Judaism and early Christianity, 2023)
"The powerful poetry of the Hebrew Psalms articulates a unique range of experience, even in translation. They explore the deepest concerns of individuals and communities. They are central to the performance of religion for both Jews and Christians. New discoveries, such as the famous Dead Sea Scrolls, have transformed our view of their role in Judaism, as has modern re-evaluation of the complicated relationship between Judaism and Christianity. Here a group of leading scholars sheds fresh light on the uses of the Psalms in post-biblical Jewish life in a multi-cultural world"--